The representative system (2020)
There are two ways to approach political representation. We can view each type of representation or each site of representation – namely a representative actor or institution – on an individual basis and study its internal dynamics. Alternatively, we can look at how different forms of representation and representative actors and institutions interact in a system of representation. In this article, I develop the second view. I make three contributions to the theory of representation from systemic thinking. Methodologically, I explain the contours of a systemic approach to political representation. Descriptively, I propose a definition of a system of representation that captures representative pluralism, distribution of representative work and different levels of representation. Normatively, I set criteria for judging the system of representation and its individual components with systemic criteria.